2013
DOI: 10.1136/tobaccocontrol-2012-050923
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative evaluation of 40 voluntary, smoke-free, multiunit, housing policy campaigns in California

Abstract: BackgroundAlthough it is legal for multiunit housing (MUH) property owners in all 50 states to prohibit smoking on their premises, including in individual units, MUH constitutes a relatively new setting to reduce exposure to secondhand smoke via voluntary smoke-free policy. This paper examines California state-funded smoke-free MUH policy campaigns between 2004 and 2010.MethodsA cross-case analysis of 40 state-funded smoke-free MUH policy campaigns was conducted via an examination of final evaluation reports s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…However, unlike in the Portland case which used landlords' competiveness to their advantage, California campaigns examined in this study found that drawing upon the collegial relationship among apartment managers, while simultaneously espousing the economic benefits of a smoke-free policy, was the most effective way to make the case for smoke-free housing. For instance, a fellow MUH owner's or manager's experience and assurance that the policy move was advantageous (particularly from an economic standpoint) was more convincing than any fact sheet or appeals from a health department or community organization (Satterlund et al, 2013). These helpful owners or managers were thus viewed as "champions" by local projects in that these individuals had strong influence and legitimacy among the community of colleagues, and were therefore integral to successful policy adoption (Satterlund et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…However, unlike in the Portland case which used landlords' competiveness to their advantage, California campaigns examined in this study found that drawing upon the collegial relationship among apartment managers, while simultaneously espousing the economic benefits of a smoke-free policy, was the most effective way to make the case for smoke-free housing. For instance, a fellow MUH owner's or manager's experience and assurance that the policy move was advantageous (particularly from an economic standpoint) was more convincing than any fact sheet or appeals from a health department or community organization (Satterlund et al, 2013). These helpful owners or managers were thus viewed as "champions" by local projects in that these individuals had strong influence and legitimacy among the community of colleagues, and were therefore integral to successful policy adoption (Satterlund et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…For instance, a fellow MUH owner's or manager's experience and assurance that the policy move was advantageous (particularly from an economic standpoint) was more convincing than any fact sheet or appeals from a health department or community organization (Satterlund et al, 2013). These helpful owners or managers were thus viewed as "champions" by local projects in that these individuals had strong influence and legitimacy among the community of colleagues, and were therefore integral to successful policy adoption (Satterlund et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Before the rule, HUD had strongly encouraged PHAs to establish smoke-free policies, and 678 had done so, generally in the Northeast, West, and Northwest (3). Many toolkits and support materials were developed to assist in the process, and state health departments have actively supported PHAs in developing smoke-free policies and provided cessation assistance to residents (21,22). Although retrospective in design, this process evaluation documents the policy-making process among the early adopters of smoke-free policies in North Carolina and Georgia.…”
Section: Intervention Approachmentioning
confidence: 99%